One-Step Surgical Approach for Treating Lens-Induced Glaucoma with Iridodialysis Following Blunt Trauma: Poster Presentation - Case Report - Resident - Haryono, Aditia Apriyanto; Gustianty, Elsa; Rifada, R Maula; Umbara, Sonie (Majalah Oftalmologi Indonesia, 2023)
Introduction : Traumatic glaucoma is one of secondary glaucoma that can be challenging to treat. Blunt trauma to the eye may result in iritis, hyphema, lens subluxation, or dislocation leading to increased intraocular pressure (IOP). Every complication needs to be addressed promptly. Here we present about one-step surgical approach to treat lens indued glaucoma with iridodialysis following blunt trauma. Case Illustration : A 65-year-old man presented with a chief complaint of blurred vision and pain in his right eye for a month following blunt ocular trauma where he was hit with piece of wood while operating a chainsaw. Ophthalmologic examination revealed RE VA of 2/60 with IOP 32 mmHg. Anterior examination revealed a shallow anterior chamber, iridodialysis 90 degrees, cloudy lens with phacodonesis (Fig 1). Patient was diagnosed with lens-induced glaucoma, lens subluxation, iridodialysis and traumatic cataract. Patient was treated with antiglaucoma agents prior to surgery. One-step surgical approach: trabeculectomy, phacoemulsification with capsular tension ring, and iridodialysis repair become the treatment of choice (Fig 2). After one month of surgery, IOP decreased to 16 mmHg without anti-glaucoma medication, final VA RE achieved 0.2 (Fig 3).DiscussionManagement of traumatic glaucoma depends on the underlying cause of increased IOP. Trabeculectomy combined with lens extraction should be considered with degree of subluxation that may cause pupillary block. Repair iridodialysis can be done using various techniques. Conclusion : Management of traumatic glaucoma can be done with trabeculectomy, lens extraction and repair iridodialysis in one-step surgery. Surgical technique should be considered depending on the patient’s eye condition.